Anthropometric and fitness normative values for young karatekas - Martinez-de-Quel, O.; Alegre, L.; Castillo-García, A.; Ayán, C. (Biology of Sport, 2021)
To provide information regarding the anthropometric and fitness profile of young karatekas and to study its evolution with age. Data from top-level karatekas were included in the analysis: 97 athletes in the U14 category (12-13 years old), 238 in cadet (14-15 years old), 261 in junior (16-17 years old) and 177 in U21 (18-20 years old), which makes a total of 773 athlete data sets. Karatekas underwent anthropometric (weight, height, body mass index and body fat percentage) and fitness (sit and reach, 20-m shuttle run, standing long jump, overhead 3-kg ball throw, 10x5-m shuttle run, and plate-tapping) assessments during the training camps organized by the Spanish National Karate Federation between 1999 and 2016. Male karatekas were taller and heavier, and performed better than females in all the fitness dimensions assessed, except for flexibility and speed of upper limb movements. The obtained cardiovascular and lower-body muscular values indicated that karatekas in this study were placed between the 80th and the 90th percentile when compared with the general population. The results of the agility, coordination and speed of upper limb movements, and flexibility tests showed that the karatekas obtained much higher scores than those observed in age-matched populations. Young karatekas show a high fitness level in comparison with the general population, especially with regards to aerobic performance, lower-body muscular power and upper-limb movement speed. Reference values of anthropometric and fitness dimensions are provided in order to be used by coaches, conditioning trainers and sport scientists when testing young male and female karatekas.